Breaking male dominance in old democracies - Dahlerup, Drude; Leijenaar, Monique (Oxford Oxford University Press, 2013)
This text provides a broad ranging critique of the continued dominance of men in the political process. It analyses the longitudinal development of women's political representation in eight old democracies, in which women were enfranchised before and around World War I: Denmark, Iceland, Germany, the Netherlands, New Jersey (USA), New South Wales (Australia), Sweden, and the United Kingdom.
Includes bibliographical references and index.
Keywords: Women -- Political activity -- Case studies; Male domination (Social structure) -- Case studies